Fermented calabash fruit-derived choline (Crescentia cujete L.) against artificial-induced ischemic stroke in rat models: Analysis of N/LR, PWR, histopathology, GM-CSF, and VEGF - Yos Adi Prakoso, Jasir Hakim Hidayah, Sitarina Widyarini (Journal of Applied Pharmaceutical Science, 2024)
Ischemic stroke is commonly caused by a thrombus and its standard treatment may have side effects. Hence, the alternative therapy against ischemic stroke requires elucidation. This study aimed to analyse the efficacy of fermented calabash fruit-derived choline (Crescentia cujete L.) (FC-C) against ischemic stroke. This study consisted of four groups: CO (sham-operated group); and the other groups (CU, FC, and PR) were artificially induced ischemic stroke, while CU (untreated); FC (2.94 mg/kg BW FC-C); and PR (496 mg/kg BW piracetam). The therapy was applied for 14 days. The neuro-deficit, blood, and brain samples were collected and the data was analysed. The results showed that the FC-C potentially affects the body weight and neuro-deficit score in rats with artificial-induced ischemic stroke compared to the other treatments. The score of neuro-deficit correlated to the percentage of infarct area in the FC group that indicated the smallest area than the others. Utilization of FC influenced the decrease of the level of N/ LR, promoted the  histopathological repair, and increased expression and level of granulocyte-macrophage colonystimulating factors (GM-CSFs) and vascular endothelial growth factor (VEGF), but not regarding the platelet-towhite blood cell ratio (PWR). In conclusion, FC-C has beneficial effects for artificial ischemic stroke in rat models. The advanced study regarding the safety of FC-C must be elucidated to support the current findings.
Keywords: Fermented calabash fruitderived choline, GM-CSF, ischemic stroke, N/LR, PWR, VEGF